Public health foresight in light of COVID-19 - EuroHealthNet (2022)
Portugal - Survey respondents and Workshop participants: Caldas de Almeida, Teresa - National Institute of Health Doutor Ricardo Jorge, Head of Health Promotion Unit; Costa, Alexandra - National Institute of Health Doutor Ricardo Jorge, Senior Technical Expert